1996
DOI: 10.1074/jbc.271.39.23634
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of Interleukin-4 Receptor α Chain Can Induce Intracellular Signaling

Abstract: The possible role of homodimerization events in intracellular signal transduction triggered by the bipartite human interleukin-4 receptor was addressed. We generated cell lines functionally expressing derivatives of the two receptor subunits alpha and gamma, which allow for a specific and background-free experimental induction of intracellular homo- and heterodimers. A heterodimer of alpha and gamma released an intracellular signal, whereas a gamma-gamma homodimer did not. Unexpectedly, we found the intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
0
65
1
Order By: Relevance
“…Cross-linking experiments with This can be explained by the presence of the IL-13R␣2 chain that we detect by RT-PCR and flow cytometry and which has been reported to bind IL-13 but not IL-4 with high affinity (43), thereby partially sequestering IL-13 in competition experiments. On the other hand, we cannot exclude the presence of IL-4R␣ homodimers in CCL202 fibroblasts in light of recent reports on chimeric receptors (44)(45)(46).…”
Section: Discussionmentioning
confidence: 73%
“…Cross-linking experiments with This can be explained by the presence of the IL-13R␣2 chain that we detect by RT-PCR and flow cytometry and which has been reported to bind IL-13 but not IL-4 with high affinity (43), thereby partially sequestering IL-13 in competition experiments. On the other hand, we cannot exclude the presence of IL-4R␣ homodimers in CCL202 fibroblasts in light of recent reports on chimeric receptors (44)(45)(46).…”
Section: Discussionmentioning
confidence: 73%
“…Mutational analyses of the cytoplasmic domain of IL-4Ra chain show that individual tyrosine residues are redundant for Stat3 activation. Signaling via homodimerization of IL-4Ra chain has been shown previously (23,47). However, a biological role for the IL-4Ra homodimers remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Human IL-4Ra cDNA was cloned into the expression vector pKCR in which the SV40 early gene promoter drove the transcription (17,23). Human IL-13Ra2 cDNA was cloned into pSecTagC (Invitrogen; ref.…”
Section: Methodsmentioning
confidence: 99%
“…27 Finally, it was shown that homodimerization of the 140-kDa IL-4 receptor ␣-chain alone can induce intracellular signaling. 34,[52][53][54] Because Stat6 is involved in the induction of transcription of the IL-4 and IL-4 receptor ␣-chain genes, 55,56 our data point at the possible existence of an autocrine loop Immunohistochemical analysis of IL-4/IL-13 receptor ␣-chain (top panels) and PDGF-␤ receptor (bottom panels) demonstrates the induction of the expression of both receptor proteins in collared carotid arteries at 6 hours after injury (C and F, respectively). For both receptor molecules, very low or undetectable immunostaining is present in sham-operated uninjured arteries (B and E, respectively) and in negative control samples (A and D, respectively).…”
Section: Discussionmentioning
confidence: 99%